Head injury criteria in child pedestrian accidents. Issue 5 (3rd September 2018) - Montoya, D.; Thollon, L.; Llari, M.; Perrin, C.; Behr, M.
ABSTRACT: Improved protection for the child pedestrian requires a precise knowledge of the biomechanics of specific injury mechanisms for this particular category of pedestrian. In the absence of tests on cadaver subjects, numerical models are a possible route of investigation for developing a predictive model for the severity of injuries. The purpose of this study was to develop an Abbreviated Injury Scale-head (AIS-head) prediction model from numerical simulations of real accident configurations between a vehicle and a child pedestrian. Fifteen real accident configurations were collected from three different databases and simulated in order to identify a realistic injury criterion. For each configuration, a complete multi-body simulation of the accident, followed by a finite element simulation of the head/hood contact, was performed. Sixteen numerical indicators of injury, related to both the kinematics and the stress distribution, were recorded at the end of each reconstruction. To assess the predictive capacity of our model, four new cases of real accidents were also simulated. Statistical analysis showed that a combination of different numerical indicators predicted the AIS-head of an accident accurately, with a mean error of 0.25.